2018
DOI: 10.1123/jpah.2016-0645
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometry-Derived Physical Activity Correlations Between Parents and Their Fourth-Grade Child Are Specific to Time of Day and Activity Level

Abstract: Background: The purpose of this study was to employ high-frequency accelerometry to explore parent-child physical activity (PA) relationships across a free-living sample. Methods: We recorded 7 days of wrist-mounted accelerometry data from 168 dyads of elementary-aged children and their parents. Using a custom MATLAB program (Natick, MA), we summed child and parent accelerations over 1 and 60 seconds, respectively, and applied published cut points to determine the amount of time spent in moderate-vigorous PA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The current study also analyzed parent-child SC relationships at weekends, on weekdays, and during the whole week. Generally, a stronger SC association was observed at weekends compared with working days, which is consistent with other studies that objectively measured PA in children and parents [35,57,58]. On the other hand, a Greek study of five-to-eight-year-old children involving 59 parent-child dyads reported a stronger parent-daughter PA relationship on weekdays compared with weekends [47].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current study also analyzed parent-child SC relationships at weekends, on weekdays, and during the whole week. Generally, a stronger SC association was observed at weekends compared with working days, which is consistent with other studies that objectively measured PA in children and parents [35,57,58]. On the other hand, a Greek study of five-to-eight-year-old children involving 59 parent-child dyads reported a stronger parent-daughter PA relationship on weekdays compared with weekends [47].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, a Greek study of five-to-eight-year-old children involving 59 parent-child dyads reported a stronger parent-daughter PA relationship on weekdays compared with weekends [47]. However, a stronger parent-child relationship generally prevails at weekends, rather than on working days [35,[57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…A moderate correlation was determined in a study examining the relationship between parent-child physical activity levels. Based on accelerometry measurements made during the day, evening, and weekend, it has been shown that children's physical activity levels correlate signi cantly with their parents' [42]. In the present study, it is considered that the inclusion of parents, peers, and teachers in the physical activity program in line with the precede-proceed model has a signi cant impact on changing children's physical activity attitudes.…”
Section: Discussionmentioning
confidence: 86%
“…During the course of the different physical activities, between parents and YPSEN, a low level of dependence or interaction is installed, although during the free time and on the weekend, this interaction is very strong. Therefore, establishing PA at the weekend and outside the school program would be much more efficient and beneficial for the physical development and psychic evolution of YPSEN (Strutz, 2018) the assumption imply that the young persons with or without special needs practicing physical activities require a different approach and at the same time in accord with the educative novelties in the pedagogical area.…”
Section: Discussionmentioning
confidence: 99%